Charging equalization of series-connected batteries - Yeo, Jia Sheen (2018)
This study is to present charge equalization method using the single-inductor multiple-output DC-DC converter to charge battery cells. The battery cells are individually charged based on individual state of charge. The SIMO DC-DC converter has a cross regulation problem due to the reduction of component. Model predictive current control method is proposed to reduce cross regulation and properly regulate the SIMO DC-DC converter. Current reference assignment algorithms are developed to provide the proper output current references for balancing the battery cells. Simulation and comparison studies are conducted to verify the performance of the proposed charge equalization method